Source-dependent effects of early-life zinc supplementation in milk on growth performance and starter intake of pre-weaned dairy calves - Rajaei-Sharifabadi, Hossein; Shamkhani, Esmaeil; Hafizi, Maryam; Mohammadi, Sajjad; Shokri, Zahra; Ahmadibonakdar, Yasaman; Seradj, Ahmad Reza (Frontiers in Animal Science, 2024)
This study aimed to evaluate the effects of milk supplementation with different zinc (Zn) sources on growth rate, starter intake, diarrhea incidence, and nutrient digestibility in dairy calves during the pre-weaning period. Forty newborn Holstein heifer calves were assigned to four treatments: control (no Zn supplementation; CON) or supplementation with 80 mg/day Zn from zinc sulfate (Zn-Sul), chelated zinc (Zn-Bon), or zinc methionine (Zn-Met). The Zn supplements were provided via milk from days 3 to 14 of age. Body weight (BW) and starter intake (SI) were monitored until weaning on day 70. Serum metabolite concentrations were determined in blood samples collected on days 15 and 70. Fecal consistency index (FCI) and frequency of medical treatments were measured during the first 21 days of life. Apparent total tract digestibility (ATTD) was determined in the 10th week of life. Although the effects of Zn supplementation on BW gain or body measurements were non-significant, a tendency for treatment × time interaction on BW was observed, with variations among the experimental groups becoming more pronounced on days 56 and 70, showing higher values in Znsupplemented calves compared to CON. SI was improved by Zn supplementation, with the greatest response in the Zn-Bon group. Compared to control, ATTD of organic matter, neutral detergent fiber, and starch tended to increase with Zn supplementation. Blood metabolites and FCI did not differ among the experimental treatments. Although no significant difference was detected between Zn-Met and CON, the frequency of medical treatment was significantly lower in Zn-Bon and Zn-Sul compared to CON calves. In conclusion, zinc supplementation in milk, particularly with the organic chelated zinc source (Zn-Bon), showed promising effects on increasing starter intake and reducing medical treatments, along with trends toward enhanced growth and nutrient digestibility in pre-weaned calves.